Is skin grafting in the patient with cutaneous sporotrichosis the definitive therapy? - Monterrubio, Nayeli Marilú López; Sánchez, Omar Sosa; Montaño, Mónica Heredia; Barrientos, Cheryl Zilahy Díaz; Tovar, Fernando Navarro; Trujillo, Hector Alejandro Carzolio (International Journal of Research in Medical Sciences, 2023)
Sporotrichosis is a subacute to chronic infection caused by the dimorphic fungal genus Sporothrix. The infection usually affects the skin and subcutaneous tissues, but occasionally it can occur at other sites, mainly in immunocompromised patients. The symptoms of extracutaneous sporotrichosis can be subtle and diagnosis is often delayed. A 54-year-old male was received, originally from Huajuapan de León, Oaxaca; who was with an established diagnosis of type 2 diabetes mellitus; later admitted by the general surgery service with a diagnosis of necrotizing fasciitis of the left and right thoracic limb. When culture was collected with Sporothrix schenckii report, management was established with itraconazole, potassium iodide and with subsequent addition of amphotericin B, with antibiotic therapy directed for superinfection by opportunistic agents. After multiple surgical cleanings with degradation of necrotic tissue, implementation of negative pressure system and amputation of nonviable fingers, it was decided to proceed with the application of skin autografts, despite the persistence of the agent in subsequent culture reports, which are fully integrated, without evidence of new ulcerodular lesions so far. Although there are currently no parameters defined in the literature that guide the time or the appropriate conditions to perform skin grafts in the areas affected by cutaneous sporotrichosis, there are, on the contrary, reports of successful cases where surgical management has been effective even in the presence of positive cultures for Sporothrix schenckii. We consider that these results open the panorama of options for the current management of cutaneous sporotrichosis, making it necessary to consider surgical management in the therapeutic range of the same, allowing the deliberation on other more conservative options before the failure of classical therapy and the imminence of amputation.